COMMUNICATIVE LANGUAGE TEACHING APPROACH IN EFL CONTEXT - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2021)
The Communicative Approach or Communicative Language Teaching (CLT) emphasizes the importance of language functions rather than focuses on grammar and vocabulary. The top ten principles of CLT are communicative interaction, meaningful practice, active involvement, positive reinforcement, choice of suitable materials, changes of pace and activity, making the teaching process enjoyable, teaching English in English, realization that mistakes are natural and that even beginners can understand when taught in the target language.